The implementation of course file management system in Universiti Teknologi MARA Pahang: an introductory study - Abd Aziz, Mohd Norafizal; Abd Aziz, Muhd Eizan Syafiq; Othman, Zainab; Othman, Mahfudzah; Hussain, Fazlin Marini; Ismail, Siti Nurbaya; Ismail, Nor Zalina; Hasnan, Mazliana; Hashim, Norhafizah (Universiti Teknologi MARA, 2009)
File Management System (FMS) provides more efficient record and data keeping in an organisation. This study discusses the effectiveness of using FMS by proposing an online system developed by the Lecturers from the Computer Science Department, Universiti Teknologi MARA (UiTM) Pahang. This system is built using web-based applications which is known as Course File Management System (CFMS). Course files are documents that translate information regarding course contents such as subject syllabus, sample of final examination papers with answer schemes and other related documents. Course files are used by academics in higher education institutions as references for certain courses. Furthermore, the academic documents kept in the course files need to be updated every semester by the resource persons. Therefore, this study discusses the development of CFMS that can help higher academic institutions manage their record keeping and tracking of the course files. This paper also discusses the stages of CFMS development and its advantages to the academics and administrators.